Producing megakaryocytes from a human peripheral blood source. Issue 5 (12th January 2016) - Ivetic, Nikola; Nazi, Ishac; Karim, Nadia; Clare, Rumi; Smith, James W.; Moore, Jane C.; Hope, Kristin J.; Kelton, John G.; Arnold, Donald M.
Abstract : BACKGROUND: Cultured megakaryocytes could prove useful in the study of human diseases, but it is difficult to produce sufficient numbers for study. We describe and evaluate the use of an expansion process to develop mature megakaryocytes from peripheral blood–derived human hematopoietic stem and progenitor cells (HSPCs). STUDY DESIGN AND METHODS: HSPCs (CD34+) were isolated from peripheral blood by positive selection and expanded using an optimal CD34+ expansion supplement. We evaluated megakaryocyte growth, maturation, and morphology in response to thrombopoietin (TPO) stimulation using flow cytometry and electron microscopy. TPO demonstrated a dose‐dependent stimulatory effect on both megakaryocyte number and maturation. RESULTS: From 90 to 120 mL of unmanipulated peripheral blood, we isolated a mean of 1.5 × 10 5 HSPCs (1.5 × 10 3 cells/mL of whole blood). HSPCs expanded nine‐fold after a 4‐day culture using an expansion supplement. Expanded cells were cultured for an additional 8 days with TPO (20 ng/mL), which resulted in a 2.9‐fold increase in megakaryocytic cells where 83% of live cells expressed CD41a+, a marker of megakaryocyte commitment, and 50% expressed CD42b+, a marker for megakaryocyte maturation. The expanded HSPCs responded to TPO stimulation to yield more than 1.0 × 10 6 megakaryocytes. This cell number was sufficient for morphologic studies that demonstrated these expanded HSPCs produced mature polyploid megakaryocytes capable of forming proplatelet extensions. CONCLUSIONS: Peripheral blood HSPCs can be expanded and differentiated into functional, mature megakaryocytes, a finding that supports the use of this process to study inherent platelet (PLT) production disorders as well as study factors that impair normal PLT production.